J‐MINT (Japan): World‐wide FINGERS network: The first global network of multidomain dementia prevention trials. (7th December 2020) - Arai, Hidenori; Sakurai, Takashi; Sugimoto, Taiki
Abstract: Background: Approximately 5 million people are living with dementia in Japan. Appropriate countermeasures should be established to reduce the incidence of dementia. The purpose of the Japan‐multimodal intervention Trial for prevention of dementia (J‐MINT) was to address the effect of a multimodal intervention in subjects with cognitive impairment. Method: J‐MINT is a RCT that will recruit 440 older people (65 to 85 years old) with high risk of dementia, defined as decreased cognitive performance in at least one of the four cognitive functional domains of memory, attention, executive function, and processing speed. Subjects will be randomized to either a group that receives usual care or a group that participates in an 18‐months multidomain intervention, consisting of exercise, nutritional counseling (visits and telephone follow‐ups by health consultants with expertise in nutrition), and cognitive training using the "Brain HQ" program. In the exercise program, the intervention group participates in activities described as "cognicise", from the combination of the words "cognition" and "exercise, " (a program developed at the National Center for Geriatrics and Gerontology, NCGG in Japan) which combines physical exercise and cognitive tasks. Additionally, diabetes, hypertension and dyslipidemia are treated in accordance with the Japanese guidelines for older patients. The primary outcome of J‐MINT is cognition, while secondary outcomes include functional status, blood‐based biomarkers reflecting β‐amyloid accumulation in the brain, omics analysis and neuroimaging (MRI). Result: We are now recruiting the participants and this study will be completed at the end of 2021. Evidence from this research is expected to inform a large‐scale, national implementation of multimodal intervention programs for older people at high‐risk of dementia. Conclusion: N/A. This study is supported by Japan Agency for Medical Research and Development.